NCAA head coach satisfaction with athletic trainers: Influence of individual athletic trainer characteristics and team factors - Larson, W.; Dearie, A.; True, L.; Richardson, B.; Lind, E. (The Sport Journal, 2020)
Considerable research exists which examines the relationship between head coach-athlete and athletic trainer-athlete. However, little is known about the perceived relationship between head coach-athletic trainer, specifically satisfaction with services provided. Purpose: This study examined head coach satisfaction with athletic trainers across National Collegiate Athletic Association (NCAA) divisions. Methods: Head coaches from a Division I, II, and III athletic department were surveyed regarding overall and dimensions of satisfaction of athletic training services. Results: No differences in Overall Satisfaction with athletic training services were noted. However, coaches assigned (a) a full-time athletic trainer reported significantly higher satisfaction in athletic trainer Knowledge/Ability than coaches with a graduate assistant and (b) a certified athletic trainer reported higher Communication scores. Moreover, Overall Satisfaction and Professionalism were different between male/female sport teams. Conclusions: Regardless of competitive level, NCAA head coaches appeared satisfied with services provided by the athletic training staff. Certain dimensions of satisfaction, however, were influenced by individual characteristics of the athletic trainer (i.e. full-time appointment; assigned certified athletic trainer). Likewise, team factors (i.e. sex of the team) also influenced satisfaction ratings with athletic training services. Applications in Sport: The findings may contribute to continued improvement of the NCAA head coach-athletic trainer relationship. Given the demands and responsibilities of each role, it is imperative to establish a trusting and positive relationship. Clearly delineating the needs and expectations both the head coach and athletic trainer are to address will only create a more productive work environment. Awareness of these findings will help inform the head coach-athletic trainer relationship by highlighting factors (e.g., access to full-time and certified athletic trainers) which can quickly facilitate the relationship. Conversely, the findings also identify potential issues (e.g., sex of the team) to address early to prevent a break down in the relationship